Application of a Cooperative Learning Model of Student Teams Achievement Division Type to Improve Student Achievement in Mathematics Lessons - Erawati, Ni Ketut; Setyawan, I Komang Agus; I Gusti Putu Partha Permana Putra (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2024)
The low mathematics learning achievement of students is due to the fact that conventional learning methods are still applied so that students are less active and less motivated in the teaching and learning process. The aim of this research is none other than to improve student learning achievement with the student teams achievement division (STAD) type cooperative learning model. This research is classroom action research. The research consists of two cycles and begins with a pre-cycle where the cycle stages consist of planning, implementation, observation and reflection. The subjects of this research were class X12 students at SMA N 1 North Kuta, totaling 45 students. The instrument used in this research was a learning achievement test. The results of the research carried out were that in Cycle I the percentage of students who completed it was 53%, then there was an increase in Cycle II to 78%, because they had met the specified classical completeness, namely 75% of the total number of students, the researcher stopped in Cycle II. Based on these results, it can be concluded that there has been an increase in student learning achievement in Mathematics learning by implementing the Cooperative learning model of the Student Teams Achievement Division (STAD) type.